Pastoral Leadership and Parish Vitality: The Effect of Pastoral Leadership on Parishioner Vitality - Frans Fandy Palinoan; Patrio Tandiangga; Hendrik Palimbo (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
Parish priest leadership plays an important role in building parish vitality and active involvement in church life. This study aims to analyze the influence of parish priest leadership on parish vitality at the parish level. The research method used a quantitative approach with a simple linear regression design. Data were collected through questionnaires involving parishioners and analyzed using SPSS software. The results of the analysis show that parish priest leadership has a significant effect on parishioner vitality with a regression coefficient of 0.449, a t-value of 7.087, and a significance of p < 0.001. The R² value of 0.175 indicates that parish priest leadership explains 17.5% of the variation in parishioner vitality, while the rest is influenced by other factors outside the model. These findings emphasize the importance of effective, relational, and empowering pastoral leadership in increasing parishioner involvement. The implications of this study highlight the need to develop an adaptive and collaborative model for pastoral leadership training and to encourage broader involvement of the laity.